2015
DOI: 10.1161/circulationaha.114.014414
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function in Survivors of Out-of-Hospital Cardiac Arrest After Target Temperature Management at 33°C Versus 36°C

Abstract: Background— Target temperature management is recommended as a neuroprotective strategy after out-of-hospital cardiac arrest. Potential effects of different target temperatures on cognitive impairment commonly described in survivors have not been investigated sufficiently. The primary aim of this study was to evaluate whether a target temperature of 33°C compared with 36°C was favorable for cognitive function; the secondary aim was to describe cognitive impairment in cardiac arrest survivors in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
127
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 41 publications
5
127
0
6
Order By: Relevance
“…The present approach to analyze blood samples collected from patients during MTH at 32°C and 37°C allowed a more accurate assessment of cooling-induced coagulation impairment. The finding that TEG results may be affected by the in vitro temperatures have already been confirmed in some studies [15,28,31,43], while in other studies it was considered insignificant [19,44]. However, in the largest randomized clinical trial conducted to date by Nielsen et al [45], it was shown that there were no differences in risk of death and neurological outcome between group with 33°C (MTH) vs. 36°C of targeted temperature management (TTM) This takes into consideration new ILCOR guidelines which recommend both therapies -MTH or targeted temperature management are nowadays the standard procedures in OHCA patients.…”
Section: Discussionmentioning
confidence: 77%
“…The present approach to analyze blood samples collected from patients during MTH at 32°C and 37°C allowed a more accurate assessment of cooling-induced coagulation impairment. The finding that TEG results may be affected by the in vitro temperatures have already been confirmed in some studies [15,28,31,43], while in other studies it was considered insignificant [19,44]. However, in the largest randomized clinical trial conducted to date by Nielsen et al [45], it was shown that there were no differences in risk of death and neurological outcome between group with 33°C (MTH) vs. 36°C of targeted temperature management (TTM) This takes into consideration new ILCOR guidelines which recommend both therapies -MTH or targeted temperature management are nowadays the standard procedures in OHCA patients.…”
Section: Discussionmentioning
confidence: 77%
“…3 Recently we reported that similar levels of cognitive impairment were found in cardiac arrest survivors treated with target temperature management as in a matched control group of myocardial infarction patients who shared the same cardiovascular risk factors. 4 Extensive literature supports the role of cardiovascular burden as the major determinant of age-related cognitive decline 11 and such burden is likely to have affected the participants of the present study as well. Since cardiac arrest often is the dramatic effect of an underlying cardiovascular disease it is likely that the cardiac arrest population will be at increased risk for a cognitive decline both before and after the arrest.…”
mentioning
confidence: 79%
“…Adding to the complexity, studies using neuropsychological tests report cognitive problems in as much as half of the survivors when assessed during the first year after the arrest. 3,4 The degree of cognitive impairment appears relatively stable over time but a few small studies have reported improvement as well as decline during the first year 5,6 leading to the frequent call for studies with longer observation times.…”
mentioning
confidence: 99%
“…In this issue of Resuscitation, Winther-Jensen et al, reports an additional analysis from the TTM trial by Nielsen et al 1,2 The current study is one in a series of recently published secondary and subgroup analyses from the TTM trial [3][4][5][6][7][8] and Winther-Jensen et al explores two relevant questions within the TTM dataset namely: (1) whether age is associated with outcomes after cardiac arrest and (2) whether the effect of targeted temperature management at 33 • C vs. 36 • C differs by age.…”
mentioning
confidence: 92%